Drain-Site Hernia Containing the Vermiform Appendix: Report of a Case - Markus Gass; Anatol Zynamon; Markus von Flüe; Ralph Peterli (Case Reports in Surgery)
The herniated vermiform appendix has been described as content of every hernia orifice in the right lower quadrant. While the femoral and inguinal herniated vermiform appendix is frequent enough to result in an own designation, port-site or even drain-site hernias are less frequently described. We report the case of a 62-year-old woman who presented with right lower quadrant pain seven years after Roux-en-Y Cystojejunostomy for a pancreatic cyst. CT scan showed herniation of the vermiform appendix through a former drain-site. A diagnostic laparoscopy with appendectomy and direct closure of the abdominal wall defect combined with mesh reinforcement was performed. Despite the decreasing use of intraperitoneal drains over the recent years, a multitude of patients had intraperitoneal drainage in former times. These patients face nowadays the risk of drain-site hernias with sometimes even unexpected structures inside.